Pengaruh Beban Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Balai Besar Pengujian Standar Instrumen Veteriner (BBPSI VETERINER) - Mutiara Rahmawati Rahman; Syahrum Agung; Anuraga Kusumah (CV. ITTC INDONESIA, 2025)
In a study entitled The Effect of Workload and Work Discipline on Employee Performance at the Veterinary Instrument Standard Testing Center (BBPSI VETERINARY). The method used is a questionnaire research instrument distributed to employees and processed using the SPSS computer application. The Workload (X1) and Work Discipline (X2) variables on Employee Performance (Y) are processed using correlation analysis, regression analysis, t-test, f-test and coefficient of determination. The results of the study indicate that the Workload (X1) variable affects the Employee Performance variable (Y), the Work Discipline (X2) variable affects the Employee Performance variable (Y), and the Workload (X1) and work discipline variables (X2) simultaneously or together affect employee performance (Y) of the Veterinary Instrument Standard Testing Center (BBPSI Veterinary).